Democracy and the disengaged: a multi-dimensional study of voter mobilization in Alabama - Carpenter, J (2016)
This thesis investigates if and how poor, mostly minority citizens can be mobilized by a campaign whose principal policy objective would materially enhance their lives by including them in a major public program. The question is put to the test through a multi-dimensional study of voter mobilization in Alabama during the 2014 election for Governor. At stake in the election was whether Alabama would expand Medicaid through the Affordable Care Act in Alabama, an issue emblematic of "submergedness" (Mettler, 2011). In order to understand the extent to which the policy was submerged—measured by knowledge and awareness of the policy, along with its key provisions—I distributed a survey to 868 Alabamians weeks before the election. The survey used the experimental design of conjoint analysis to test which aspects of the policy were most persuasive among the target population. Additionally, I performed a randomized field experiment across the four major metropolitan areas of Alabama, micro-targeting 6,021 registered voters living in the "Coverage Gap," citizens who could gain health insurance if Medicaid were expanded. The campaign yielded negligible effects on voter turnout among subjects in the Coverage Gap, even though the interventions shifted voter knowledge, “surfacing” the policy. In addition to the survey and field experiments, this research benefits from qualitative insights gathered in 22 semi-structured interviews conducted among poor Alabamians, many of whom were uninsured. From these interviews, it became clear that the political disengagement of the poor is deeply entrenched, prohibitive of policy-based mobilization. Disengagement is driven by a complex mix of barriers to registration and perceptions of political inefficacy based on interpretations of extant policy designs. These results have important implications for our understanding of the limitations of policy-based mobilization, suggesting that more attention must be paid to how current policies shape predispositions for mobilization.